EFEKTIVITAS MODEL PEMBELAJARAN ICARE DENGAN PENERAPAN PETA KONSEP TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Reskiah Ilyas; Azhari; Fatimah; Hari Aningrawati Bahri (Universitas Sulawesi Barat, 2019)
This study aims to describe the effectiveness of the ICARE learning model by applying concept maps to the mathematics learning outcomes of SMP Negeri 1 Wonomulyo students with a population of 211 people, consisting of 7 classes. The sample of this study were 29 people, namely class VIII A SMP Negeri 1 Wonomulyo. The research instrument used was a learning achievement test, student response questionnaire, student activity sheet and learning achievement sheet. Analysis used descriptive and inferential statistical analysis. The results showed that student learning outcomes in mathematics taught by the ICARE learning model with the application of concept maps were in the high category with a classical mastery level reaching 93.10% or there were 27 students who scored â‰¥ 75, and the average value of learning mathematics through initial tests before and tests after learning with the ICARE model with the application of concept maps has increased significantly. Student activities at each meeting showed that the eight categories observed fulfilled effective criteria. This achievement shows that the expected student activities are fulfilled. Student responses taught by the ICARE learning model with the application of concept maps are in the positive category with an average score of student responses reaching 3.92. The application of the ICARE model with the application of concept maps in learning mathematics in the classroom, provides opportunities for students to exchange ideas with friends or teachers in terms of finding and building their own knowledge in students, where with these conditions gave birth to positive responses in mathematics learning. Thus the ICARE learning model with the application of the concept map was declared effective in class VIII of SMP Negeri 1 Wonomulyo, Polewali Mandar Regency.